Content production technologies - Hasegawa, Fumio; Hiki, Haruo (John Wiley & Sons, 2004)
We are currently in a digital content era. With the increase in circulation of multimedia content globally via the internet it has lead to the need for reuse of content stored in archives; the utilisation of newly stored materials; partially finished broadcasting programmes and finished content. This book proposes to show solutions to these numerous content issues. It will discuss large scale archives for significant content and a retrieval method for large scale archives and remote editing. The book will also examine the protection of intellectual property rights, which is one of the most.